Synopsis of Pselaphinae (Coleoptera: Staphylinidae) of the Mascarene Islands, with description of a new species of Leiochrotella Jeannel, 1953 from Réunion - Hlaváč, Peter; Kocian, Matúš (Zootaxa, 2018)
The new species, Leiochrotella lequettei Hlaváč & Kocian, sp. n., is described from Réunion. A synopsis of all Pselaphinae of the Mascarenes (Réunion, Mauritius and Rodriguez) is provided.